Positive mental imagery, emotion regulation and depressive symptoms in individuals with alcohol use disorder - Rydzewska, M.; Zaorska, J.; Kopera, M.; Kobyliński, P.; Trucco, E. M.; Wiśniewski, P.; Marciniuk, A.; Żmigrodzka, A.; Jakubczyk, A. (Frontiers in Psychiatry, 2025)
IntroductionsEmotion regulation, depressive symptoms and mental imagery have both been linked to alcohol use disorder (AUD). However, the association between these factors have not been investigated within a group of individuals with AUD.ObjectivesThe primary aim of this study was to investigate associations between emotion regulation, depressive symptoms and positive mental imagery among individuals with AUD and healthy controls (HCs).MethodsThe study sample included 136 individuals with AUD and 80 HCs. Severity of depressive symptoms was assessed with the Beck Depression Inventory (BDI) and emotion dysregulation - with the Difficulties in Emotion Regulation Scale (DERS). The Flexible Emotion Regulation Scale (FlexER) was used to measure flexible emotion regulation and the Prospective Imagery Task (PIT) - to assess positive mental imagery.ResultsVividness of positive mental imagery was significantly lower in the AUD group compared to HC group, while emotional intensity of positive mental imagery was significantly higher in the AUD group. Higher vividness of positive mental imagery was associated with lower emotional dysregulation in the AUD group and with higher flexibility of emotion regulation among both groups. Emotional intensity of positive mental imagery was positively correlated with flexibility of emotion regulation in the AUD group, but negatively correlated with flexibility of emotion regulation among HCs. In the AUD group, both vividness and emotional intensity of positive mental imagery were significantly associated with lower severity of depressive symptoms.ConclusionsEnhancing positive mental imagery abilities might be a promising strategy in the treatment of AUD.